The Development and Application of the RAND Program Classification Tool : The RAND Toolkit, Volume 1 - Joie D. Acosta, Gabriella C. Gonzalez (RAND Corporation, 2014)
Despite the recent drawdown of troops in Iraq, the increased pace of deployments over the past decade, longer deployments, and frequent redeployments have resulted in significant mental health problems among service members. Among those who had been deployed to Iraq and Afghanistan as of October 2007, approximately one-fifth reported symptoms consistent with current posttraumatic stress disorder (PTSD) or major depression, and about the same number reported having experienced a probable TBI while deployed (Tanielian and Jaycox, 2008). In the wake of the 2007 report of the DoD Task Force on Mental Health (Department of Defense Task Force on Mental Health, 2007), DoD has implemented numerous programs, interventions, and policies to address the increased prevalence of these conditions and their effects on service members and their families. As these efforts have proliferated, it has become more challenging for DoD to monitor these programs and to avoid potential duplication of effort. To support DoD efforts in this area, RAND compiled a comprehensive catalog of relevant programs and created a taxonomy for them (see Weinick et al., 2011). In developing the catalog of DoD programs related to psychological health and TBI, RAND encountered a fundamental problem: the lack of a single, clear, universally accepted definition of the term program.